Client-Side Authorized Deduplication In Cloud Using PoW - Mounika, P; Jyothsna, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an effective and emerging technology for storing huge amounts of data. Most of the organizations and people are using cloud for storing various types of data. The critical challenge is to maintain the stored data without any redundancies due to billing nature of cloud. Deduplication is a popular technique used to remove duplicate copies from cloud. Existing deduplication techniques using convergent encryption does not support for authorized duplicate check. Authorized duplicate check is essential to protect the sensitivity and integrity of data that is stored. In this paper, the client-side authorized deduplication is implemented using hybrid cloud where the duplicate check is performed at client-side which improves data security and reduce network bandwidth. In this work, duplicate check for a file is performed by a token generated by private cloud based on privilege of user issued during system initialization and file content. Each file uploaded to the cloud is also bounded by a token to specify which kind of users is allowed to perform the duplicate check and access the files. The user is able to find a duplicate for this file if and only if there is a copy of this file and a matched privilege. To prevent unauthorized access, a secure proof of ownership (PoW) protocol is also implemented to provide the proof that the user indeed owns the same file instead of small information of file when a duplicate is found. It makes overhead to minimal compared to the normal convergent encryption and file upload operations.